Evaluation of Lysinibacillus sphaericus as a nutrient enhancer during fire-impacted soil re-plantation (2017)
More than twenty fires over the last ten years have affected El Noviciado estate located in Cerro Majuy, Cota, Colombia; fires led to soil nutrient lost and infertility. Lysinibacillus sphaericus, a gram-positive, mesophilic and spore-forming bacterium, can be used in soil nutrients enrichment within re-plantation processes, given its ability to fix nitrogen, nitrify and solubilize phosphorus, increasing soil nutrients that are taken for plant growth. In this study, we evaluated the soil-enrichment potential of L. sphaericus by monitoring the nutrients content of a selected fragment of soil in El Noviciado estate. For this purpose, we added a mixture of L. sphaericus OT4b.31, OT4b.49, CBAM5, III(3)7 and 2362 strains and determined the ammonium, nitrites, nitrates, phosphorus an indoleacetic acid concentrations in soil. Also, we transplanted seedlings of Alnus acuminata sbsp. acuminata, which is a native model plant known for its restoration effect. Results indicated that soil with L. sphaericus added presented higher ammonium, nitrites, nitrates, phosphorus and indoleacetic acid concentrations than control soil. Additionally, the analysis for the presence of a molybdenum transporter gene showed band size products between 400-500 bp., indicating the existence of the nitrogenase traditional complex in all the L. sphaericus strains evaluated.